Forecasting the Production Results of Medicine Horticultural Plants (Biofarmacies) in North Sumatra in 2020 and 2021 Using Double Exponential Smoothing Brown Method - Sinaga, Lia Herna; Siregar, Rosman (Talenta Publisher, 2022)
Indonesian medicinal plants have a high contribution to world drug production. North Sumatra is one of provinces that produces a variety of traditional medicinal plants. The data in this study is secondary data obtained from the Central Statistics Agency of North Sumatra which is data on the amount of production of medicinal horicultural plants (biopharmaceuticals) from 2007-2019 using the method Double Exponential Smoothing Brown. The purpose of this research is to get the parameters α and shape forecasting equation that can be used to estimate the amount of production of the total production of horticultural crops medicin from 2006 to 2018 by using the size of the precision of the forecasting Mean absoulte Percentage Error in the method of Double Exponential Smoothing Brown. The parameter α is best used to predict the amount of horticultural crop production of medicinal was 0.24 with a yield forecasting in 2020 amounted to 8,454,007.24 kg and in 2021 amounted to 7,779,411.27 kg.